Analisa Akresi, Erosi dan Perubahan Tata Guna Lahan Secara Spasial Pasca Terbentuknya Konstruksi Jetty Kuala Jangka - Fahmi, Mirza; Majuar, Edi; Reza, Muhammad; Yusniyanti, Erna; Syarwan, Syarwan; Iskandar, Iskandar (Politeknik Negeri Lhokseumawe, 2023)
As time goes by the impact of the construction of the Jetty construction which is located on Kuala Term Beach, Bireuen Regency around the coast causes accretion and erosion every year. To find out how big the impact caused by accretion and erosion on the coast was analyzed using Qgis software with sources based on satellite imagery. The purpose of this study was to determine the amount of accretion and erosion caused by sedimentation and eroded areas, to determine the success of coastal vegetation, and to determine the success of jetty construction on land use around the coast. The amount of accretion that occurred in 2006 was 302,140 m2, in 2009 it was 532,585 m2. Whereas in 2014 it was 385,239 m2, in 2015 it was 552,830 m2, in 2016 it was 526,214 m2 and in 2017 it was 541,591 m2. This resulted in the advancement of the coastline impacting an increasing area. Furthermore, in 2006 coastal erosion also affected the coastline of 472,178 m2, in 2009 it was 592,996 m2, in 2014 it was 361,477 m2, in 2015 it was 496,354 m2 and in 2017 304,765 m2 was the area that was eroded. As a result accretion and erosion also have an impact on changes in land use. Such as coastal vegetation, settlements, traders, and pond areas. According to the results of interviews with the community, dredging is very necessary to prevent shallowing in the estuary so that it does not interfere with the shipping lanes of fishing boats.